Acoustic assessment of bat activity at wind turbines: Comparing the performance of different bat detectors - Simon, Ralph; Brinkmann, Robert; Hochradel, Klaus; Mages, Jürgen; Nagy, Martina; Niermann, Ivo; Stiller, Florian; Behr, Oliver (Conference on Wind energy and Wildlife Impacts, 2015)
In Central Europe, acoustic monitoring of bat activity has become the most common method to assess the collision risk of bats at wind turbines. Often, acoustic data are used to develop turbine specific ‘bat friendly’ operational algorithms that reduce the collision risk. A major problem of acoustic monitoring is that there are many different methods (e.g. monitoring at the nacelle vs. at ground level, different microphone setups) and different devices (e.g. bat detectors) used to conduct such acoustic surveys at turbines. As these methods and systems vary in their acoustic properties, the bat activity measured strongly depends on the methods/devices used. Precise estimation of bat activity is crucial to assess the collision risk and to develop suitable algorithms to reduce the risk of bat collisions, but also to avoid needless shutdowns of turbines because of algorithms that are too conservative. Here, we compare different methods and detectors that are being used to assess the acoustic bat activity wind turbines, in particular maintenance requirements, downtimes, acoustic properties, and bat activity level recorded. We did acoustic surveys at the nacelle of 16 wind turbines in 8 wind parks in four geographical regions in Germany in 2012 using different systems simultaneously. We used Anabat SD1 (Titley Scientific), Batcorder 1.0 (ecoObs) and UltraSoundGate (Avisoft Bioacoustics) detectors. In the lab, we also measured the frequency responses and directional sensitivity of the detector microphones. We compared the acoustic activity of bats as presence/absence data for 10-minute-intervalls and found that with the settings we used the relative activity of species and species groups was quite similar for different detectors but for most species or species groups Anabat SD1 and UltraSoundGate recorded bat activity that was twice as high as the activity measured with the Batcorder. This shows that for different detectors different models have to be used to precisely predict risk of collision for the bats and deduce suitable algorithms. We found that the employment of different microphone types with different directional characteristics and the use of various detector settings (i.e. various detection thresholds) are one of the main reasons for different estimations of bat activity. We further discuss detection volumes of detectors deduced from frequency response measurements and methods for a consistent calibration.

A low cost - high accuracy multisensor array for bat localization - Hochradel, Klaus; Dorsch, Philipp; Häcker, Timm; Hohler, Tino; Sutor, Alexander; Lerch, Reinhard (International Bat Research Conference, 2016)
Many behavioral studies demand knowledge of the distribution or location of bats in space. Our research group investigated the behavior of bats in close proximity to the nacelle of wind turbines. Therefore, we measured the distribution of bats with help of stereo infrared cameras. Systems able to provide this information are expensive, complicated and require a specialist in the field for assembly and data acquisition. Our aim was to design an inexpensive and easy to use system to localize bats that, in addition, allows long recording periods. In order to gain maximum information the localization system contains different sensor technologies. On one hand, it includes active infrared-stereo-cameras to localize bats optically and on the other hand each ultrasonic bat call can be recorded and localized by multilateration with multiple novel ultrasonic microphones. We developed a calibration procedure to align the optical and the acoustical system. The developed setup with its dimension of 1x1m is tripod mountable and the costs sum up to 5000 EUR with the goal to decrease costs to 2000 EUR. To achieve this, we programmed a FPGA to record the ultrasonic bat signals to be independent of proprietary hardware. Furthermore, we implemented a novel detection algorithm for ultrasonic bat calls which allows to run different detection techniques simultaneously in real-time. This algorithm was optimized for the FPGA and provides precise distinction between bat calls and noise to reduce post processing efforts and disk space. Both systems offer an accuracy of ±20 cm within a radius of 20 m. Since the optical and the acoustical system are calibrated, their results can be combined to improve not only accuracy but also reliability.
Keywords: Microphone Array; Bat; Localization; Stereo Camera

A model for the prediction of bat collision rates at wind energy turbines - Korner-Nievergelt, Fränzi; Baumbauer, Lothar; Brinkmann, Robert; Hochradel, Klaus; Hurst, Johanna; Mages, Jürgen; Nagy, Martina; Niermann, Ivo; Reers, Hendrik; Simon, Ralph; Weber, Natalie; Behr, Oliver (Conference on Wind energy and Wildlife Impacts, 2015)
In Europe, a widespread method to mitigate bat collisions at wind energy turbines is to stop the rotor during times with high collision rates. To do this efficiently, high collision rates need to be predicted in order to save bats from being killed. Also, periods with low collision risk have to be identified to minimize losses in energy production. We present a model that reliably predicts turbine specific collision rates as well as identifies times with low collision risk. The model is a hierarchical zero-inflated Poisson model that includes a Bernoulli model for collision risk and a Poisson model for the collision rate. We developed the model based on a large empirical data set including daily carcass searches at 30 turbines during 3 months, and continuous recordings of acoustic bat activity and wind speed at the nacelle of the turbine at 70 turbines during 7 months. We corrected for the imperfect detection of carcasses within the model. The model is particularly useful for predicting bat collision rates during times of the year with low bat activity and little empirical data on collision rates.

‘Bat-friendly’ operation of wind turbines – the current status of knowledge and planning procedures in Germany - Behr, Oliver; Baumbauer, Lothar; Hochradel, Klaus; Durst, Johanna; Mages, Jürgen; Nagy, Martina; Korner-Nievergelt, Fränzi; Niermann, Ivo; Reers, Hendrik; Simon, Ralph; Weber, Natalie; Brinkmann, Robert (Conference on Wind energy and Wildlife Impacts, 2015)

Bats are attracted to wind turbines – determining the distribution of bats by a stereo thermal camera system - Hochradel, Klaus; Adomeit, Uwe; Mages, Jürgen; Simon, Ralph; Stiller, Florian; Behr, Oliver (Conference on Wind energy an Wildlife Impacts, 2015)
Attraction of bats to wind turbines is frequently discussed to be one of the reasons for high fatality rates. Thus, knowledge on activity distribution is vital to improve methods to reduce fatalities. However, no research has yet been conducted on the influence of existing wind turbines on the behavior of bats. We have seen different approaches to reduce fatalities such as ultrasonic deterrents or ‘bat-friendly’ operational algorithms, most of which share the assumption of an equally distributed bat activity in the rotor swept area. We quantified bat activity at wind turbines as a function of distance to the nacelle with a stereo thermal camera system. Stereo images were recorded in 2008 and 2012 during ten nights at six turbines at four sites in Germany. The turbines were also equipped with at least one acoustic bat detector installed in the nacelle. We triangulated the position of each recorded bat in absolute coordinates with the nacelle of the wind turbine as origin and the rotor diameter as field of view and correlated the results with the acoustic records. Activity decreased exponentially with increasing distance to the nacelle and converged to a constant level. This level describes the normal distribution of bats in free air space without the influence of wind turbines. Bat activity in close proximity (<10m) could not be determined since the nacelle covers most of the field of view. The distribution of bats was based on a total amount of 4468 triangulated bat positions. We used the distribution of bats triangulated around the nacelle to calculate a novel scaling factor accounting for varying rotor diameters of wind turbines that can be used for calculating ‘bat-friendly’ operational algorithms. As of yet, scaling was based on the assumption that bat activity is equally distributed. When using a uniform distribution, the scaled activity is largely overestimated which reduces the efficiency of the operational algorithms. The relation between bat activity and distance to the nacelle not only enabled us to improve the scaling for operational algorithms but also suggests that bats are attracted to wind turbines.

Development of a multisensor array for localizing bats in space - Hochradel, Klaus; Hohler, Tino; Becher, Andreas; Wildermann, Stefan; Sutor, Alexander (Journal of Physics: Conference Series, 2018)
We present a novel multisensor array to track flight paths of bats in space. Our array is designed to be portable and, thus, field applicable. Eight microphones are employed to localize each echolocation call, whereas two cameras provide continuous information on the flight path between the calls. To reduce costs and, thus, make it available for low-budget research the array was developed from scratch including a novel acoustic signal recording and processing hardware. Our developed acoustic hardware is the first system to sample eight microphone channels synchronously at 1 MS/s/CH with 16 Bit resolution without the necessity of computers or laptops. All eight signals from the ultrasonic microphones are not only recorded but also processed in real time in the frequency as well as time domain to determine the existence of echolocation calls. Only relevant acoustic signal are recorded which enables long term deployments of the array. During the acoustic signal acquisition, the system records images of two infrared cameras at 12 Hz and, in addition, several environmental factors such as temperature, humidity and illumination. Recorded datasets can be associated with a global position and time-stamp through a GPS module and matched to the GPS coordinate system with a three-axis accelerometer. The overall system (microphones, cameras and sensors) was designed to be affordable, easy to use in the field on battery power and without the necessity of an additional laptop. Without cost optimization and only small quantity we reached a prize below 1000 EUR for a complete system.

Dynamic performance of dielectric elastomers utilized as acoustic actuators - Hochradel, Klaus; Rupitsch, Stefan; Sutor, Alexander; Lerch, Reinhard; Vu, Duc Khoi; Steinmann, Paul (Applied Physics A-Materials Science & Processing, 2012)
We report on the frequency dependent behavior of dielectric elastomer actuators (DEA). The introduced smart material actuators consist of 3M™'s elastomer VHB™4905 (9469) and a compliant, sputtered copper electrode on each side. The presented experiments on these compounds contain the active tuning of their resonance frequency and their application as acoustic actuators.We are able to decrease the membranes' eigenfrequency by 30% with an electrical offset potential. Alternatively, if an alternating signal is applied, sound pressure levels up to 130 dB in an enclosed volume of 28 ccm are achieved. In order to verify the results, a numerical simulation is introduced incorporating the two physical fields involved: electrical and mechanical. © 2012 Springer-Verlag.
UnivIS-Import:2015-04-14:Pub.2012.tech.FT.FT-TM.dynami

Experimenteller Test der ledermausfreundlichen Betriebsalgorithmen - Behr, Oliver; Brinkmann, Robert; Hochradel, Klaus; Hurst, Johanna; Mages, Jürgen; Naucke, Andreas; Nagy, Martina; Niermann, Ivo; Reers, Hendrik; Simon, Ralph; Weber, Natalie; Korner-Nievergelt, Fränzi (Reduktion des Kollisionsrisikos von Fledermäusen an Onshore-Windenergieanlagen (RENEBAT II), 2015)

Fehlerbetrachtung und Kalibrierung eines portablen Mikrofonarrays zur multilateralen Ortung von Ultraschall-Fledermausrufen - Hochradel, Klaus; Dorsch, Philipp; Häcker, Timm; Sutor, Alexander; Lerch, Reinhard (DAGA - 42. Jahrestagung für Akustik, 2016)
Keywords: Microphone Array; Stereo Camera; Calibration

Methoden akustischer Erfassung der Fledermausaktivität an Windenergieanlagen - Simon, Ralph; Hochradel, Klaus; Mages, Jürgen; Nagy, Martina; Naucke, Andreas; Niermann, Ivo; Weber, Natalie; Behr, Oliver (Reduktion des Kollisionsrisikos von Fledermäusen an Onshore-Windenergieanlagen (RENEBAT II), 2015)
Zentrales Ergebnis des vorausgegangenen Forschungsvorhabens RENEBAT  I war die Berechnung des Schlagrisikos für Fledermäuse an Windenergieanlagen (WEA) aus der automatisiert gemessenen akustischen Aktivität. Die Höhe der Fledermausaktivität (z.B. als Aufnahmen pro Stunde) hängt dabei stark von den eingesetzten Detektoren und gewählten Detektoreinstellungen ab. In RENEBAT I wurden der Batcorder (ecoObs GmbH) und der Anabat SD1 (Titley) für die Datenerfassung im Feld verwendet. In RENEBAT II wurde neben diesen Detektoren auch der Detektor UltraSoundGate (USG) der Firma Avisot Bioacoustics eingesetzt. Zunächst berechneten wir theoretisch vorhersagbare Unterschiede aus den physikalischen Eigenschaten der Detektoren, insbesondere der Mikrofone. So berechneten wir Erfassungsreichweite und -volumen anhand des Frequenzgangs und der Richtcharakteris tik der Mikrofone. Abhängig von der Frequenz des Fledermausrufs war das abgedeckte Volumen des Avisot-USGs 3 bis 3,5 mal so groß wie das des Batcorders. Bei der Triggerung (Auslösung) einer Aufnahme arbeiten das USG und der Batcorder nach einem ähnlichen Prinzip, wohingegen Titleys Anabat keine Selektion von Rufen vornimmt, sondern eine Daueraufnahme von Nulldurchgangsdaten aufzeichnet. Die theoretischen Vorhersagen wurden mit unterschiedlichen praktischen Experimenten veriiziert. Sowohl der Anabat SD1 Detektor als auch das UltraSoundGate wurden an jeweils acht Anlagen getestet, der Batcorder parallel zu jeweils einem der anderen Detektoren an 16 WEA. Durch den parallelen Einsatz war es möglich, Unterschiede in der Empindlichkeit und der daraus 6.3 Anabat System (Titley) . . . . . . . . . . . . . . . . . . . . . . . 62 7 Performance der Geräte im Vergleich . . . . . . . . . . . . . . . . . . . 63 7.1 Frequenzgang und Richtcharakteristik der Mikrofone und Mikrofonscheiben. 64 7.2 Bestimmung des Erfassungsvolumens . . . . . . . . . . . . . . . . 67 7.3 Überprüfung der theoretischen Erfassungsreichweite an einer WEA mit Hilfe einer Flugdrohne . . . . . . . . . . . . . . . . . . . . . . . . . 69 7.4 Bestimmung der Einlussfaktoren der Triggerung verschiedener akustischer Erfassungssysteme . . . . . . . . . . . . . . . . . . . . . . . . . 71 7.5 Laufzeiten und Ausfälle der Detektoren. . . . . . . . . . . . . . . . 75 7.6 Empindlichkeit für Störungen . . . . . . . . . . . . . . . . . . . 76 7.7 Aufgezeichnetes Artenspektrum . . . . . . . . . . . . . . . . . . . 78 8 Literatur. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 79 Einleitung 41 resultierenden Einschätzung der Aktivität für die unterschiedlichen Detektoren zu quantiizieren. In RENEBAT II wurden die Detektorsysteme im Unterschied zu RENEBAT I nicht ofen in der Gondel montiert, sondern in einem Schaltschrank aus Stahl vorinstalliert. In einem Pilotversuch wurde zudem an einzelnen Anlagen ein alternativer Aubau des UltraSoundGates von Avisot getestet, bei dem sich nur die Mikrofonscheibe in der Gondel befand und die Aufzeichnungseinheit am Anlagenfuß installiert war. Das Mikrofonsignal wurde mithilfe eines langen Kabels, das im Anlagenturm verlegt wurde, nach unten geleitet. Alle drei Detektoren erwiesen sich als geeignet für ein Gondelmonitoring zeigten jedoch deutliche Unterschiede in der Erfassungsreichweite, der Anzahl von Störungsaufnahmen, der Dauer von Ausfallzeiten und der Anzahl von Aufnahmen mit Fledermausrufen.

Mitigating Bat Mortality with Turbine-Specific Curtailment Algorithms: A Model Based Approach - Behr, Oliver; Brinkmann, Robert; Hochradel, Klaus; Mages, Jürgen; Korner-Nievergelt, Fränzi; Niermann, Ivo; Reich, Michael; Simon, Ralph; Weber, Natalie; Nagy, Martina (Wind Energy and Wildlife Imteractions, 2017)
Keywords: Acoustic Activity; Bats; Collision Risk; Central Europe; Operational mitigation; Wind Turbine

Reducing bat fatalities at wind turbines in central Europe -How efficient are bat-friendly operation algorithms in a fieldbased experiment? - Behr, Oliver; Hochradel, Klaus; Mages, Jürgen; Nagy, Martina; Korner-Nievergelt, Fränzi; Niermann, Ivo; Simon, Ralph; Stiller, Florian; Weber, Natalie; Brinkmann, Robert (Conference on Wind Power and Environmental Impacts (CWE), 2013)
Reducing bat fatalities at wind turbines in central Europe – How efficient are bat-friendly operation algorithms in a field-based experiment? Here we present data from an ongoing field-test of ‘bat-friendly’ operational algorithms for wind turbines. The algorithms trade off the reduction in collision risk against the loss in revenue resulting from mitigation. Algorithms are turbine-specific and are based on data of acoustic bat activity, wind speed, month, and time of night that were previously recorded in 2008 and 2010 at 72 randomly selected turbines in Germany. 18 of these turbines are now part of the ongoing experiment. To develop the bat-friendly operational algorithms we first modelled acoustic bat activity from the month, time of night, wind speed, and a turbinespecific factor coding the level of bat activity. Next, we used a mixture model to estimate the collision risk from acoustic bat activity. Both models were combined to estimate the collision risk using only wind and time as predictive variables. During times of high collision risk, rotors are stopped to avoid bat fatalities. Times of high risk are defined by a turbine-specific cut-in wind speed that varies with month and time of night. We are currently running our bat-friendly algorithms in an experimental set-up at 16 wind turbines at 8 sites (2 turbines each) in 4 different geographical regions in Germany and at 2 turbines at one site in France. The two turbines within each site are running with and without algorithms in alternating one-week intervals from July to September of 2012. All turbines in the experiment are equipped with at least 2 of 3 different acoustic detectors at the nacelle (Anabat SD1, Avisoft Ultra Soundgate, and Batcorder) that sample acoustic bat activity continuously during the night. Additionally, the area under the turbines is searched for animal fatalities each day during the entire time of the experiment. We will quantify the long-term variability of bat activity comparing acoustic data from 2012 and 2008. From the fatality data we will be able to draw con- NATURVÅRDSVERKET RAPPORT 6546 Book of Abstracts 34 clusions on the effectiveness of the algorithms (loss in revenue per reduction in bat fatality) and on the total cost for their implementation. We will compare the number of bat fatalities predicted for the specific operational algorithm to the number of carcasses found after correcting for search biases. Finally, and most importantly we will develop guidelines and practical examples for the quantification and mitigation of bat fatalities by bat-friendly operation of wind turbines in central Europe.

Three-dimensional localization of bats: visual and acoustical - Hochradel, Klaus; Häcker, Timm; Hohler, Tino; Becher, Andreas; Wildermann, Stefan; Sutor, Alexander (IEEE Sensors Journal, 2019)
Keywords: Acoustics; Cameras; Microphone arrays; Hardware; Sensors; Data acquisition; Microphone; Array; Stereo Camera; Infrared; automation; Ultrasound; Source localization; Bat

Wärmeoptische 3D-Erfassung von Fledermäusen im Rotorbereich von Windenergieanlagen - Hochradel, Klaus; Adomeit, Uwe; Heinze, Nicolai; Nagy, Martina; Stiller, Florian; Behr, Oliver (Reduktion des Kollisionsrisikos von Fledermäusen an Onshore-Windenergieanlagen (RENEBAT II), 2015)
Im vorhergehenden Forschungsvorhaben (im Folgenden „RENEBAT  I“) kam weltweit erstmals ein stereo-wärmeoptisches Erfassungssystem zum Einsatz, mit dem die akustische Erfassung von Fledermäusen im Gondelbereich von Windenergieanlagen (im Folgenden „WEA“) validiert werden konnte. Dieses System ermöglicht es, die 3D-Flugbahnen von Fledermäusen im Gondelbereich von WEA zu bestimmen. Zusammen mit den akustischen Aufnahmen der in der Gondel installierten Detektoren können auf diese Weise Rückschlüsse auf die Reichweite der Detektoren gezogen werden. Im hier dargestellten Forschungsprojekt (im Folgenden „RENEBAT II“) erweiterten wir den aus RENEBAT  I vorliegenden Wärmebilddatensatz um vier Erfassungsnächte. In jeweils zwei Nächten wurde die Fledermausaktivität in zwei verschiedenen Naturräumen erfasst. Aus den Wärmebilddaten der Naturräume D12 und D14 konnten insgesamt 18 bzw. 19 Flugbahnen innerhalb eines Abstands von 60 m zur Gondel vermessen werden (4468 bestimmte Fledermauspositionen). Die Analyse dieser Flugbahnen gab Hinweise auf wahrscheinliches Inspektionsverhalten von Fledermäusen in Gondelnähe. Außerdem wurde eine Kollision mit einem Rotorblatt aufgezeichnet. Im Fokus der Auswertung stand die Verteilung der Aufenthaltswahrscheinlichkeit von Fledermäusen im Rotorbereich von WEA. Die Kombination der Daten aus 2008 und 2012 zeigte eine exponentielle Abnahme der Aufenthaltsdichte mit zunehmendem Abstand zur Gondel. Die Aktivitätsdichte konvergierte dabei gegen einen Minimalwert, von dem wir annehmen, dass er der Aktivität im freien Lutraum entspricht. Basierend auf der gemessenen Verteilung berechneten wir Skalierungsfaktoren für das Schlagrisiko an WEA in Abhängigkeit vom Rotordurchmesser (falls dieser von dem der in RENEBAT  I beprobten WEA abweicht). Die in RENEBAT  I entwickelte Methode berechnet das Schlagrisiko für WEA mit etwa 70 m Rotordurchmesser. Bei WEA mit hiervon abweichendem Rotor würde daher das Schlagrisiko über- (bei weniger als 70 m Rotordurchmesser) bzw. unterschätzt (bei mehr als 70 m). Würde man bei der Korrektur für den Rotordurchmesser vereinfachend von einer Gleichverteilung der Fledermausaktivität im Rotorbereich ausgehen, so würde das Schlagrisiko z. B. für Anlagen mit 100 m Rotordurchmesser sehr hoch angesetzt werden. Im Unterschied dazu berücksichtigen wir bei den hier entwickelten Skalierungsfaktoren die Abnahme der Fledermausaktivität mit größerem Abstand zur Gondel, wodurch sich das geschätzte Schlagrisiko für große Anlagen deutlich reduziert. Wir validierten die berechneten Skalierungsfaktoren, indem wir z. B. die Aufnahmen vor und hinter der Gondel getrennt voneinander analysierten. Auch hier ergab sich eine Einleitung 83 exponentielle Abnahme der Fledermausdichte mit zunehmendem Abstand zur Gondel. Messungen der Schlagrate an Anlagen mit größerem Rotordurchmesser könnten zur weiteren Validierung der Ergebnisse beitragen.